Does board gender diversity affect corporate cash holdings?. (25th July 2019) - Atif, Muhammad; Liu, Benjamin; Huang, Allen
Abstract: This paper examines whether board gender diversity affects corporate cash holdings using S&P 1500 index firms in the US for the period 2006–2015. We document a significantly negative relationship between board gender diversity and cash holdings. We also find a strong negative effect of female independent directors consistent with monitoring function. Moreover, in accordance with the critical mass theory, we find a negative effect of female directors' presence and voice on cash holdings. Our findings are robust to alternative econometric specifications, alternative measures of cash holdings and corporate governance, difference‐in‐differences, propensity score matching, and two‐stage least squares. This study offers useful insights into the current global debate on gender diversity and its implications for firms.